1990
DOI: 10.1080/02724936.1990.11747429
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular accidents (strokes) in children with sickle cell disease residing at high and low altitudes of Saudi Arabia

Abstract: In a 3-year period, eight cases of cerebrovascular accident were seen out of 400 patients with sickle cell disease residing at high and low altitudes of Asir Province of Saudi Arabia. They were all Saudi nationals and comprised five boys and three girls of ages ranging from 3.5 to 9 years. They had varied clinical presentations of their cerebrovascular accident. Cranial computed tomography in seven of them showed abnormality in the region of the middle cerebral circulation. Management and some suggested factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Cerebrovascular accident (stroke) was observed in five patients (9.43%), all 10 years of age and under, and none of them died. Annobil et al from southern Saudi Arabia reported stroke in 2% of patients, 14 and an incidence of 7%-17% has been reported by Mercouri et al from London. 15 In contrast to our study, Balkaran et al from Jamaica reported 35% mortality in patients with cerebrovascular accident.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrovascular accident (stroke) was observed in five patients (9.43%), all 10 years of age and under, and none of them died. Annobil et al from southern Saudi Arabia reported stroke in 2% of patients, 14 and an incidence of 7%-17% has been reported by Mercouri et al from London. 15 In contrast to our study, Balkaran et al from Jamaica reported 35% mortality in patients with cerebrovascular accident.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge there have only been a few reported cases of stroke in children with SCD in Saudi Arabia. 7,8 Our study probably presents the largest number of strokes reported in children with SCD in Saudi Arabia. We found a relatively high prevalence of stroke among our patients (10%), as compared to other studies (7%-8%).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The majority of our patients were male, which is consistent with other studies. 3,7 The reason for male predominance is unknown. The youngest patient in our study was a three-year-old male, and the age group mostly affected was between three and 10 years, also consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, patients differ from African Americans phenotypically and have fewer episodes of stroke, priapism, and leg ulcers and a higher prevalence of splenomegaly. 14,[70][71][72] This might be related to differences in HbF levels or coinheritance of ␣-thalassemia.…”
Section: Southwestern Provincementioning
confidence: 99%